Literature of the management of physical education based on the Scopus database: A bibliometric review - Feby Elra Perdima; Muhammad Kristiawan; Davi Sofyan; Nagoor Meera Abdullah; Nurhuda (UIR Press, 2022)
Effective management is required to aid students in positively developing their character and skills during the physical education learning process. The goal of this study is to conduct a bibliometric analysis of management in physical education publications that have been published in Scopus. The study focuses on the productivity of publishing management in physical education papers on Scopus, on the most prestigious journals, authors, and articles, and on an analysis of keywords that frequently appear in management in physical education articles published on Scopus. The search yields 598 documents that were published in the Scopus database between 2017 and 2021. The majority of publications are written by Webster, C.A., who has six published articles. The most active scientific journal is the Journal of Physical Education and Sport, which has 26 published articles. With 41 links, the United States has the most total link strength of any nation. With 122 instances,